A hybrid photovoltaic and water/air based thermal(PVT) solar energy collector with integrated PCM for building application. (November 2022) - Li, Jianhui; Zhang, Wei; Xie, Lingzhi; Li, Zihao; Wu, Xin; Zhao, Oufan; Zhong, Jianmei; Zeng, Xiding
Abstract: Based on the different requirements of solar energy integrated with buildings, a hybrid photovoltaic and thermal solar energy collector with integrated phase change material (PVT-PCM) have been developed. The thermal system combines air-based and water-based conditions to meet the building heat demand in different seasons. In addition, PCM is used to absorb the heat that was not taken away by the thermal system. And the vessel is optimized to enhance its thermal conductivity. The results of cross-season test show that the overall efficiency of the system is 39.4%, and the energy-saving efficiency is 64.2%. The system controls the temperature and utilizes the heat through the thermal system. The economic analysis and energy saving potential of the system in low latitude areas are analyzed. The results show that the additional payback period of the system is 13.1 years. And based on the local energy structure, the maximum CO2 emission can be reduced by 156.1 kg/year. The optimization systems BPVT and CPVT are proposed, and simulation and analysis results show that BPVT is more valuable for further exploration. Compared with the traditional PV system, PVT-PCM system improved the comprehensive utilization rate of solar energy and has a broader research and development prospect. Highlights: A new PVT system with switchable working status is designed. ●The system has potential to reduce CO2 emissions combined with energy structures. ●The 13.1 years additional investment payback period show good application potential. ●The optimization systems are proposed and predicted for further exploration.